Pentingnya Penguasaan Bahasa Asing bagi Pengembangan Sektor Pariwisata di Wonosobo - Fajarsari, Amalia; Setiansah, Mite; Santoso, Edi (Jurnal Pewarta Indonesia, 2024)
Wonosobo, as a developing tourist city, has great potential to attract both domestic and international tourists, especially with its natural beauty and tourist attractions like the Dieng Plateau. However, one of the main challenges faced is the limitation of local human capital, particularly in foreign language proficiency, which is necessary to provide optimal services to international tourists. This research aims to analyze the role of foreign language proficiency in the development of the tourism sector in Wonosobo using the frameworks of Innovation Diffusion Theory, Agenda Setting Theory, and Human Capital Theory. This study employs a qualitative method with a case study approach, involving in-depth interviews with various stakeholders, including local government, tourism operators, and local media. The research results show that proficiency in foreign languages, especially English, plays a crucial role in improving service quality, attracting more foreign tourists, and creating new job opportunities in the area. In addition, the strategies implemented by the government and the support of local media in establishing the agenda for foreign language proficiency have proven effective in raising public awareness. In conclusion, mastery of foreign languages is a crucial innovation in strengthening the competitiveness of Wonosobo's tourism in the global market, as well as contributing to more inclusive and sustainable regional economic growth.